DC traction power substation using eighteen-pulse rectifier transformer system - Chuen Ling Toh; Chee Wei Tan (Institute of Advanced Engineering and Science, 2021)
Twelve-pulse rectification system had been widely integrated in today’s DC traction power sub-station (DC-TPSS). This configuration had successfully mitigated low order harmonic distortion. As some research findings had confirmed that the dc voltage and current ripple factors may further minimize by increasing the number of rectification pulses to 18, 24, or 36. This paper had presented a simulation study to investigate the prospect of implementing an eighteen-pulse rectification system in a DC-TPSS. The theory of phase-shifting transformer used to produce an 18-pulse rectifier is presented with simulation verification. Simulation result shows that 3.69% of grid current distortion index is recorded without installing any filters. In addition, the dc voltage and current ripple may also be further reduced for about 30% compared to a conventional twelve-pulse rectification system.